Study of logistics and supply chain management of teak wood product industry in the northern part of Thailand - Diloksumpun, Piyawat; Arunwarakorn, Suratwadee (Kasetsart Journal of Social Sciences, 2021)
The purpose of this research was to study the structure of supply chain and logistics system, cost analysis, operation problems, and make recommendations for efficient improvement in whole supply chain of teak wood product industry. The methodology comprised data collection, literature review, direct observation, and structural interview from the northern part of Thailand. The results showed the structure of the supply chain both in users and products, and the flow of process in forestry plantation operation, collaboration between sawmills and forestry plantations, and overall operations of cooperatives were mentioned. The study presented problems and suggestions as follows: (1) Physical flow of teak products: the policy and the law were main problems; therefore, the government should analyze such and make up-to-date; (2) Complicated track and trace of logs and processing: new machinery and technology to support such should be developed; (3) Information flow lacked coordinated system, duplicated document operation, and outdated accounting system: integrated information system should be developed; (4) Community, problem in forming cooperatives and lack of confidence of private sector to invest: the government should educate and build confidence; (5) Value addition, teak retailers lack processing technology and market demand; (6) Lack of research to develop various product formats; and (7) Underpricing from middleman, which requires cooperation between public and private sector to solve the problems. As a consequence, such can lead to improving and developing the planning of teak plantation in the northern part of Thailand, such as transformation process, value added and cost effectiveness in the operation of whole teak supply chain.